Physical and Biological Properties of Waters in the Region of the Antarctic Peninsula and Adjacent Basins of the South Atlantic - Morozov, Eugene (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue is dedicated to collating recent research on the Atlantic sector of the Southern Ocean and Antarctica Peninsula region. This Issue also considers the spreading of Antarctic Bottom Water. Papers in this issue are focused on field research of the physical properties and ecology of this key region of the Southern Ocean. The main objects of the study are the properties of seawater, currents, ecosystems, and biological communities in the South Atlantic, the Powell Basin of the northwestern Weddell Sea, the Bransfield Strait, and the Antarctic Sound. The Antarctic marine ecosystem is unique in terms of its biodiversity and high productivity of the basic trophic levels of the ecosystem. This ecosystem is efficiently used by organisms such as seabirds, seals, and whales that feed on Antarctic krill.